CK2 Regulation: Perspectives in 2021 - Scott E. Roffey; David W. Litchfield (Biomedicines, 2021)
The protein kinase CK2 (CK2) family encompasses a small number of acidophilic serine/threonine kinases that phosphorylate substrates involved in numerous biological processes including apoptosis, cell proliferation, and the DNA damage response. CK2 has also been implicated in many human malignancies and other disorders including Alzheimer′s and Parkinson’s diseases, and COVID-19. Interestingly, no single mechanism describes how CK2 is regulated, including activation by external proteins or domains, phosphorylation, or dimerization. Furthermore, the kinase has an elongated activation loop that locks the kinase into an active conformation, leading CK2 to be labelled a constitutively active kinase. This presents an interesting paradox that remains unanswered: how can a constitutively active kinase regulate biological processes that require careful control? Here, we highlight a selection of studies where CK2 activity is regulated at the substrate level, and discuss them based on the regulatory mechanism. Overall, this review describes numerous biological processes where CK2 activity is regulated, highlighting how a constitutively active kinase can still control numerous cellular activities. It is also evident that more research is required to fully elucidate the mechanisms that regulate CK2 and what causes aberrant CK2 signaling in disease.